A silicon-based negative electrode composite material and its preparation method and application

By adopting a combined structure of porous silicon-carbon material and composite cladding in lithium-ion batteries, the volume expansion and cycle stability of silicon-carbon composite materials in lithium-ion batteries is solved, and higher battery cycle performance and the first time are achieved Cyclic Curlun efficiency.

CN118970021BActive Publication Date: 2025-02-11SHENZHEN SOLID ADVANCED MATERIALS TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411443631.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-11
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In the prior art, during the long-term cycle of lithium-ion batteries, the carbon layer cannot withstand the long-term volume deformation of silicon particles and breaks, affecting the capacity and service life of the electrode, and at the same time, the ionic conductance of the oxide coating layer. Poor properties affect the kinetic process of lithium ions.

Method used

Using porous silicon carbon material composed of porous carbon and nano-amorphous silicon as the core, combining an amorphous carbon layer and a composite cladding layer containing metal oxides and solid electrolytes, silicon-based negative electrodes are prepared by chemical vapor phase method and liquid phase cladding technology. Composite material.

Benefits of technology

It effectively reduces the volume expansion of silicon-carbon composite materials, improves battery circulation performance and first-time circulation Coulomb efficiency, extends the service life of the electrode, and improves the kinetic process of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118970021B_ABST
    Figure CN118970021B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion batteries, and discloses a silicon-based negative electrode composite material, a preparation method thereof, and an application thereof. The silicon-based negative electrode composite material includes a core, an intermediate layer, and a composite coating layer from the inside to the outside, the core is a porous silicon-carbon material composed of porous carbon and nano-amorphous silicon deposited in the internal pores of the porous carbon, the intermediate layer is an amorphous carbon layer, and the composite coating layer includes a metal oxide and a solid electrolyte. The silicon-based negative electrode composite material of the present invention buffers the volume expansion of silicon through the porous silicon-carbon material, the amorphous carbon layer maintains structural integrity, the oxide in the composite coating layer is completely attached to the surface of the carbon layer, and the continuous generation of the SEI layer can be avoided. The solid electrolyte has high lithium ion conductivity and accelerates the kinetic process of lithium ions. Therefore, the silicon-based negative electrode composite material of the present invention not only effectively reduces the volume expansion of the silicon-carbon composite material, but also improves the battery cycle performance and the first cycle coulomb efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a silicon-based negative electrode composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of electric vehicles, energy storage technology and portable electronic products, lithium-ion batteries (LIBs) have attracted widespread attention as indispensable power storage devices. Silicon is a promising alloy anode material with a suitable operating voltage (0.1-0.4 V), a high theoretical specific capacity (4200 mAh g -1 ), and abundant reserves on Earth. However, silicon (Si) has several disadvantages as an anode active material. Si is a typical semiconductor material with an electronic conductivity (<10 -3 S cm -1 ) cannot meet the requirements of fast kinetic reactions. In addition, more than 300% expansion occurs during the charge / discharge process of Si, which leads to structural collapse and loss of electrical contact between active Si nanoparticles and current collectors. Since Si continuously forms a solid electrolyte interface (SEI) layer on the interface during the cycle, it consumes lithium ions in the electrolyte, causing rapid decay of battery capacity. Based on the above two reasons, the commercialization process of Si is hindered.

[0003] The coating technology on the surface of silicon negative electrode is an effective method to improve the stability of negative electrode materials. On the one hand, by modifying the interface on the surface of Si negative electrode, the lithium ions consumed by the formation of "natural" SEI layer are reduced, and the occurrence of side reactions in the battery is reduced; on the other hand, the coating layer can maintain the stability of Si structure during the cycle process and improve the cycle life of the battery.

[0004] In the prior art, patent CN107845797A discloses a method for preparing a nano-silicon-based negative electrode composite material: nanocrystalline graphite is placed in a vacuum rotary tube furnace, heated to 850°C, and then a silicon source is added to prepare a precursor, and then the precursor is mixed evenly with a carbonaceous binder in a mixer, and then placed in a vacuum rotary tube furnace, heated to 600°C under the protection of nitrogen, and the prepared material is crushed and screened to prepare a nano-silicon-based negative electrode composite material. From the research results of silicon-carbon composite materials, the core-shell structure material has good cycle stability, indicating that carbon coating has an obvious buffering effect on the volume deformation of nano-silicon particles. However, during the long cycle of the battery, the carbon layer in the carbon-coated Si / C core-shell structure will still be unable to withstand the long-term volume deformation of silicon particles and break, which directly affects the capacity and service life of the electrode. It can be seen that due to the huge volume change of Si during the lithium insertion process, the carbon layer cannot maintain the stability of the structure and cannot avoid the continuous generation of the SEI layer.

[0005] Patent CN105958023A provides a method for coating Si negative electrode with alumina, wherein the Si negative electrode coated with alumina is obtained after pre-oxidation of nano-Si and mixing with aluminum powder for heat treatment, and then treated with acid or oxidant. The thickness of the alumina coating layer can be controlled by adjusting the process conditions of nano-Si pre-oxidation. The obtained Si@Al2O3 negative electrode material has a more stable surface structure, a higher capacity retention rate, good cycle stability, and excellent electrochemical properties during the lithium insertion and extraction process. However, when oxide is used as the coating layer of Si, the ionic conductivity of the oxide itself is relatively poor, which will affect the kinetic process of lithium ions during the lithium insertion / extraction process. In the first cycle, some lithium ions react with lithium ions and consume some lithium ions, thereby affecting the first cycle coulombic efficiency.

[0006] In view of the defects existing in the above-mentioned prior art, how to optimize the structure of silicon-carbon composite materials while reducing the volume expansion of silicon-carbon composite materials and improving battery cycle stability and first cycle coulombic efficiency is a difficult problem that needs to be solved urgently in this field.

[0007] Therefore, the existing technology still needs to be developed and improved. Summary of the invention

[0008] In view of the above-mentioned deficiencies in the prior art, the present invention provides a silicon-based negative electrode composite material and a preparation method and application thereof, aiming to solve the technical problem of how to optimize the structure of the silicon-carbon composite material to reduce the volume expansion of the silicon-carbon composite material and simultaneously improve the battery cycle performance and the first cycle coulombic efficiency.

[0009] Specifically, the technical solution of the present invention is as follows:

[0010] The first aspect of the present invention is to provide a silicon-based negative electrode composite material, which includes a core, an intermediate layer and a composite coating layer from the inside to the outside, wherein the core is a porous silicon-carbon material composed of porous carbon and nano-amorphous silicon deposited in the internal pores of the porous carbon, the intermediate layer is an amorphous carbon layer, and the composite coating layer includes a metal oxide and a solid electrolyte.

[0011] Optionally, in the composite coating layer, the metal oxide is aluminum oxide or titanium oxide, and the solid electrolyte includes one or more of lithium silicate, lithium aluminate, lithium titanate and lithium phosphate.

[0012] Optionally, the amorphous carbon layer has a thickness of 10-15 nm; the composite coating layer includes aluminum oxide and lithium aluminate, and the composite coating layer has a thickness of 1-4 nm.

[0013] The second aspect of the present invention is to provide a method for preparing the silicon-based negative electrode composite material, comprising the steps of:

[0014] S1. Using a chemical vapor method to prepare a porous silicon-carbon material by reacting porous carbon with silane;

[0015] S2, performing chemical vapor deposition on the surface of the porous silicon-carbon material to obtain porous silicon-carbon coated with a carbon layer;

[0016] S3. Dispersing the porous silicon carbon coated with the carbon layer in a solvent, adding aluminum isopropoxide and lithium acetate, and then heating to perform liquid phase coating on the surface of the porous silicon carbon coated with the carbon layer, and then calcining at a high temperature in an inert atmosphere to form a composite coating layer containing aluminum oxide and lithium aluminate, so as to obtain the silicon-based negative electrode composite material.

[0017] In step S1, optionally, the step of preparing a porous silicon-carbon material by reacting porous carbon with silane using a chemical vapor deposition method comprises: placing the porous carbon in a chemical vapor deposition furnace, introducing an inert gas, heating the temperature to 400-700°C, and introducing silane gas to deposit nano-amorphous silicon in the internal pores of the porous carbon to obtain the porous silicon-carbon material.

[0018] Wherein, optionally, the porous carbon includes one or more of resin porous carbon, bioporous carbon, petroleum-based porous carbon and coal-based porous carbon.

[0019] Optionally, the silane gas is monosilane or disilane; and the inert gas is nitrogen or argon.

[0020] Optionally, the size of the internal pores of the porous carbon is 0.1-100 nm.

[0021] Optionally, the particle size of the nano-amorphous silicon is 0.1-50 nm.

[0022] In step S2, optionally, chemical vapor deposition is performed on the surface of the porous silicon-carbon material to obtain a porous silicon-carbon coated with a carbon layer, comprising: placing the porous silicon-carbon material in a chemical vapor deposition furnace, introducing an inert gas at a rate of 1 to 20 L / min, heating the material to 500 to 800°C, and then introducing acetylene gas at a rate of 1 to 10 L / min for a ventilation time of 50 to 500 minutes to obtain the porous silicon-carbon coated with the carbon layer.

[0023] Wherein, optionally, the inert gas is nitrogen or argon.

[0024] In step S3, optionally, the mass percentage of the aluminum isopropoxide in the porous silicon-carbon material is 1% to 3%.

[0025] Optionally, the molar ratio of the lithium acetate to the aluminum isopropoxide is 1:1 to 1:3.

[0026] In step S3, optionally, the heating method is water bath heating, and the heating temperature is 60-80°C.

[0027] In step S3, optionally, the temperature of the high-temperature calcination is 300-600° C., and the time of the high-temperature calcination is 2-4 hours.

[0028] The third aspect of the present invention is to provide an application of the silicon-based negative electrode composite material prepared by the preparation method of the silicon-based negative electrode composite material in a lithium-ion battery.

[0029] Beneficial effects:

[0030] The present invention provides a silicon-based negative electrode composite material and a preparation method and application thereof, wherein the silicon-based negative electrode composite material includes, from the inside to the outside, a porous silicon-carbon material composed of porous carbon and nano-amorphous silicon deposited in the internal pores of the porous carbon, an amorphous carbon layer, and a composite coating layer composed of metal oxides and solid electrolytes. The porous silicon-carbon material in the silicon-based negative electrode composite material of the present invention serves as a core, which can buffer the volume expansion generated by silicon, and the amorphous carbon layer in the middle further maintains the integrity of the silicon-carbon structure. At the same time, the metal oxide in the composite coating layer is completely attached and coated on the surface of the amorphous carbon layer, which can avoid the continuous generation of the SEI layer, and the solid electrolyte in the composite coating layer has a high lithium ion conductivity, reduces the loss of lithium ions, and accelerates the kinetic process of lithium ions. Therefore, the silicon-based negative electrode composite material provided by the present invention achieves effective reduction of the volume expansion of the silicon-carbon composite material, while improving the battery cycle performance and the first cycle coulomb efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic structural diagram of the silicon-based negative electrode composite material provided by the present invention, wherein 1: porous silicon-carbon material, 2: amorphous carbon layer, 3: pores, and 4: composite coating layer.

[0032] Figure 2 This is a transmission electron microscope image of the silicon-based negative electrode composite material prepared in Example 1 of the present invention, with a scale of 20 nm.

[0033] Figure 3 This is the X-ray photoelectron spectrum (XPS) of the silicon-based negative electrode composite material prepared in Example 1 of the present invention.

[0034] Figure 4 This is a comparison chart of the electrochemical impedance spectra measured for the silicon-based negative electrode composite material prepared in Example 1 of the present invention and the control group composite materials prepared in Comparative Examples 1 and 3.

[0035] Figure 5 A comparison chart of battery cycle test results of the silicon-based negative electrode composite materials prepared in Examples 1 to 3 of the present invention.

[0036] Figure 6 A comparison chart of battery cycle test results of the silicon-based negative electrode composite material prepared in Example 1 of the present invention and the control group composite material prepared in Comparative Examples 1-2.

[0037] Figure 7 This is a comparison chart of battery cycle test results of the silicon-based negative electrode composite material prepared in Example 1 of the present invention and the control group composite material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0038] The present invention provides a silicon-based negative electrode composite material and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the scope of protection of the present invention.

[0039] An embodiment of the present invention provides a silicon-based negative electrode composite material, which includes, from the inside to the outside, a core, an intermediate layer and a composite coating layer, wherein the core is a porous silicon-carbon material composed of porous carbon and nano-amorphous silicon deposited in the internal pores of the porous carbon, the intermediate layer is an amorphous carbon layer, and the composite coating layer includes a metal oxide and a solid electrolyte.

[0040] In some embodiments, in the composite coating layer, the metal oxide is aluminum oxide or titanium oxide, and the solid electrolyte includes one or more of lithium silicate, lithium aluminate, lithium titanate and lithium phosphate, but is not limited thereto.

[0041] In some preferred embodiments, the amorphous carbon layer has a thickness of 10-15 nm; the composite coating layer includes aluminum oxide and lithium aluminate, and the composite coating layer has a thickness of 1-4 nm.

[0042] A simple metal oxide coating layer can easily cause an increase in specific surface area due to uneven coating, as well as problems such as its insulation performance and consumption of lithium ions during the first lithium insertion process. The silicon-based negative electrode composite material provided by the present invention is designed with a composite coating layer comprising metal oxide and solid electrolyte, wherein the metal oxide is completely attached to the surface of the silicon-carbon negative electrode, which can avoid the continuous generation of the SEI layer. At the same time, the solid electrolyte has high lithium ion conductivity, which accelerates the kinetic process of lithium ions from the electrolyte to Si. Therefore, the composite coating layer will not cause an increase in the specific surface area of ​​the material, and has good ionic conductivity and surface chemical modification, which can promote interfacial ion charge transfer, avoid the consumption of lithium ions during the lithium insertion process and affect the first effect.

[0043] In some specific embodiments, the thickness of the composite coating layer is 1-4 nm, preferably, the thickness of the composite coating layer can be 2 nm. If the composite coating layer is too thin, it cannot completely cover the battery during the cycle, and it is easy to break during the cycle and cannot avoid the continuous growth of the SEI layer; if the composite coating layer is too thick, the lithium insertion path is too long, which affects the lithium insertion kinetics of Si.

[0044] The embodiment of the present invention provides a method for preparing the silicon-based negative electrode composite material, comprising the steps of:

[0045] S1. Using a chemical vapor method to prepare a porous silicon-carbon material by reacting porous carbon with silane;

[0046] S2, performing chemical vapor deposition on the surface of the porous silicon-carbon material to obtain porous silicon-carbon coated with a carbon layer;

[0047] S3. Dispersing the porous silicon carbon coated with the carbon layer in a solvent, adding aluminum isopropoxide and lithium acetate, and then heating the surface of the porous silicon carbon coated with the carbon layer to perform liquid phase coating, and calcining at a high temperature in an inert atmosphere to form a composite coating layer containing aluminum oxide and lithium aluminate, thereby obtaining the silicon-based negative electrode composite material.

[0048] In step S1, in some embodiments, the step of preparing a porous silicon-carbon material by reacting porous carbon with silane using a chemical vapor deposition method comprises: placing the porous carbon in a chemical vapor deposition furnace, introducing an inert gas, heating the temperature to 400-700°C, and introducing silane gas to deposit nano-amorphous silicon in the internal pores of the porous carbon to obtain the porous silicon-carbon material.

[0049] Conventional silicon-carbon is to embed Si in a carbon substrate, relying on the properties of carbon itself to buffer the volume expansion of Si during the cycle, so the space that can accommodate the expansion of Si during the cycle is very limited, which easily causes the silicon-carbon material to break during the cycle. The porous silicon-carbon material synthesized by the present invention is a porous carbon material with reserved micropores and mesopores for buffering, which can better buffer the volume expansion of silicon, and a carbon layer is coated on the surface of the silicon-carbon material to maintain the integrity of the silicon-carbon material structure.

[0050] In some specific embodiments, the porous carbon includes one or more of resin porous carbon, bioporous carbon, petroleum-based porous carbon and coal-based porous carbon, but is not limited thereto.

[0051] In some specific embodiments, the silane gas is monosilane or disilane; the inert gas is nitrogen or argon, but is not limited thereto.

[0052] In some embodiments, the size of the internal pores of the porous carbon is 0.1-100 nm.

[0053] In some embodiments, the particle size of the nano-amorphous silicon is 0.1-50 nm.

[0054] In step S2, in some embodiments, chemical vapor deposition is performed on the surface of the porous silicon-carbon material to obtain a porous silicon-carbon coated with a carbon layer, comprising: placing the porous silicon-carbon material in a chemical vapor deposition furnace, introducing an inert gas at a rate of 1 to 20 L / min, heating the temperature to 500 to 800°C, and then introducing acetylene gas at a rate of 1 to 10 L / min for a ventilation time of 50 to 500 minutes to obtain the porous silicon-carbon coated with the carbon layer.

[0055] In some embodiments, the inert gas is nitrogen or argon, but is not limited thereto.

[0056] In step S3, in some embodiments, the mass percentage of the aluminum isopropoxide in the porous silicon-carbon material is 1% to 3%.

[0057] In some embodiments, the molar ratio of the lithium acetate to the aluminum isopropoxide is 1:1 to 1:3.

[0058] In step S3, in some embodiments, the heating method is water bath heating, and the heating temperature is 60-80°C.

[0059] In step S3, in some embodiments, the temperature of the high temperature calcination is 300-600° C., and the time of the high temperature calcination is 2-4 hours.

[0060] The embodiment of the present invention provides an application of the silicon-based negative electrode composite material prepared by the preparation method of the silicon-based negative electrode composite material in a lithium-ion battery.

[0061] The scheme of the present invention is further described below with specific embodiments.

[0062] Example 1

[0063] (1) 1500 g of porous carbon (particle size D50 distribution in the range of 5-10 μm) was added to a chemical vapor deposition furnace, and nitrogen was introduced at a flow rate of 14 L / min for 60 min. The temperature in the furnace was raised to 520 °C, and monosilane was introduced at a flow rate of 3 L / min. The silane ventilation time was set to 500 min to obtain a silicon-carbon composite material.

[0064] (2) The obtained silicon-carbon composite material is placed in a chemical vapor deposition furnace, nitrogen is introduced at a rate of 14 L / min, the temperature is raised to 550°C, and acetylene gas is then introduced at a rate of 3 L / min. The ventilation time of acetylene gas is set to 200 min, thereby obtaining porous silicon-carbon coated with a carbon layer.

[0065] (3) Disperse 10 g of porous silicon carbon coated with a carbon layer in 400 ml of anhydrous ethanol, add 3 wt.% of aluminum isopropoxide (i.e., aluminum isopropoxide accounts for 3% of the mass of the porous silicon carbon material), and then gradually add lithium acetate dropwise (the molar ratio of lithium acetate to aluminum isopropoxide is 1:3). Use a liquid phase coating method to evenly coat the surface of the porous silicon carbon coated with the aluminum isopropoxide and lithium acetate mixed solution in an 80°C water bath. Heat the coated material to 500°C in a nitrogen atmosphere for 3.0 h to convert the aluminum oxide on the surface into a lithium aluminate solid electrolyte coating layer.

[0066] Example 2

[0067] Compared with Example 1, the difference is that the molar ratio of lithium acetate to aluminum isopropoxide is 1:2.

[0068] Example 3

[0069] Compared with Example 1, the difference is that the molar ratio of lithium acetate to aluminum isopropoxide is 1:1.

[0070] Comparative Example 1

[0071] Compared with Example 1, the difference is that step (2) is not included, and only step (3) is used to wrap the composite coating layer outside the porous silicon-carbon material.

[0072] Comparative Example 2

[0073] Compared with Example 1, the difference is that physically mixed nano-silicon and amorphous carbon materials are used to replace the porous silicon-carbon material, and no pores are reserved inside.

[0074] Comparative Example 3

[0075] Compared with Example 1, the difference is that lithium acetate is not added in step (3), that is, the coating layer outside the carbon layer of the porous silicon carbon is only an aluminum oxide layer.

[0076] like Figure 1As shown, the composition of the silicon-based negative electrode composite material from the inside to the outside includes: 1 porous silicon-carbon material, 2 amorphous carbon layer and 4 composite coating layer (including metal oxide and solid electrolyte). Among them, the core of the silicon-based negative electrode composite material is a porous silicon-carbon material, and there are 3 pores inside, which can alleviate the volume change during the Si lithium insertion process, and alleviate the stress generated thereby, and prevent the collapse of the material structure; the second layer structure is an amorphous carbon layer, and the carbon layer is tightly coated on the surface of the porous silicon-carbon material to prevent the electrolyte from infiltrating into the pores to produce SEI to continuously consume lithium ions and affect the material capacity. At the same time, the carbon layer can also maintain the stability of the silicon-carbon structure and prevent the rupture of the silicon-carbon material. The third layer is a composite coating layer, which can quickly transfer lithium ions from the electrolyte to the inside of the silicon-carbon material and accelerate the kinetic process of lithium ion conduction. The solid electrolyte in the composite coating layer is an electronic insulating layer, which can prevent the silicon-carbon material from continuously reducing the electrolyte due to the rupture of the SEI layer during the cycle, causing the SEI layer to continue to thicken and consume lithium ions.

[0077] like Figure 2 As shown, it can be seen that in the two types of coating layers of the silicon-based negative electrode composite material, the thickness of the middle amorphous carbon layer is about 12 nm, and the thickness of the composite coating layer on the outer surface is about 2 nm.

[0078] like Figure 3 As shown, XPS is used to characterize the composite coating of the silicon-based negative electrode composite material. From the characterization results, it can be seen that in the Al 2p spectrum, Al / Al2O3 peaks appear at 75.4eV and 75.87eV, indicating the presence of inorganic component aluminum oxide in the composite coating; in the Li 1s spectrum, Li-Al and Li-Si peaks appear at 55.7eV and 56.6eV, respectively, indicating that lithium aluminate is also present in the composite coating.

[0079] Figure 4 SEI diagram of silicon-based negative electrode composite material. Figure 4 (a) is an impedance spectrum of the silicon-based negative electrode composite material obtained in Example 1 before electrochemical cycling. It can be seen from the figure that compared with the porous silicon carbon only coated with a carbon layer, the presence of the composite coating layer can slightly reduce the resistance of the material; Figure 4(b) is the impedance spectrum of the obtained material after 5 cycles after button cell assembly. Its impedance is composed of ohmic resistance, SEI impedance in the high-frequency region, charge transfer impedance in the medium-frequency region, and lithium ion diffusion impedance in the low-frequency region. It can be seen that after the cycle, the SEI impedance, charge transfer impedance, and lithium ion diffusion impedance of the silicon-based negative electrode composite material containing a composite coating of aluminum oxide and lithium metaaluminate are significantly reduced, which well explains that the composite coating can improve the cycle performance of the material. At the same time, the silicon-carbon composite material in the outermost layer of comparative example 3 containing only an aluminum oxide coating layer will increase the impedance of the material in the later stage of the cycle. This may be because although the aluminum oxide coating layer can construct a stable SEI layer, it is inert and has poor ionic conductivity, which causes the impedance of the silicon-carbon material to increase during the cycle.

[0080] like Figure 5 As shown, by comparing the cycle performance of silicon-based negative electrode composite materials with composite coating layers of different thicknesses, it can be seen that with the increase of the thickness of the composite coating layer, the first effect of the silicon-carbon negative electrode material shows a gradually decreasing trend, and the cycle capacity retention rate also gradually decreases, indicating that the diffusion distance of lithium ions is prolonged as the thickness of the solid electrolyte coating layer increases.

[0081] like Figure 6 As shown, the battery cycle life of the silicon-based negative electrode composite material with a composite coating layer prepared in Example 1 of the present invention is significantly improved, especially the composite coating layer with a suitable thickness can significantly improve the battery performance, and compared with the silicon-carbon material without reserved pores, the cycle stability of the composite material with porous silicon-carbon material as the substrate is significantly optimized, indicating that the stress and structural stability generated by the expansion of the silicon-based negative electrode composite material during cycling are significantly improved. This may be because the solid electrolyte in the composite coating has high ionic conductivity at room temperature, thereby improving the charge transfer at the negative electrode / electrolyte interface.

[0082] like Figure 7 As shown, compared with the alumina coating layer, after the alumina is partially lithiated to form a composite coating layer, the silicon-based negative electrode composite material prepared in Example 1 of the present invention significantly improves the cycle performance and the first cycle coulombic efficiency.

[0083] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A silicon-based negative electrode composite material, characterized in that: The silicon-based negative electrode composite material comprises a core, an intermediate layer and a composite coating layer from the inside to the outside, wherein the core is a porous silicon-carbon material composed of porous carbon and nano-amorphous silicon deposited in the internal pores of the porous carbon, the intermediate layer is an amorphous carbon layer, and the composite coating layer comprises aluminum oxide and lithium metaaluminate; The thickness of the amorphous carbon layer is 10-15 nm; the thickness of the composite coating layer is 1-4 nm; The silicon-based negative electrode composite material is prepared by the following preparation method: S1. Using a chemical vapor method to prepare a porous silicon-carbon material by reacting porous carbon with silane; S2, performing chemical vapor deposition on the surface of the porous silicon-carbon material to obtain porous silicon-carbon coated with a carbon layer; S3, dispersing the porous silicon carbon coated with the carbon layer in a solvent, adding aluminum isopropoxide and lithium acetate, heating the surface of the porous silicon carbon coated with the carbon layer to perform liquid phase coating, and calcining in an inert atmosphere to form a composite coating layer containing aluminum oxide and lithium aluminate, thereby obtaining the silicon-based negative electrode composite material; The mass percentage of the aluminum isopropoxide to the porous silicon-carbon material is 1% to 3%; the molar ratio of the lithium acetate to the aluminum isopropoxide is 1:1 to 1:

3.

2. The silicon-based negative electrode composite material according to claim 1, characterized in that: In step S1, the step of preparing a porous silicon-carbon material by chemical vapor deposition with porous carbon and silane comprises: placing the porous carbon in a chemical vapor deposition furnace, introducing an inert gas, heating the porous carbon to 400-700° C., introducing silane gas, and depositing nano-amorphous silicon in the pores inside the porous carbon to obtain the porous silicon-carbon material; Wherein, the porous carbon includes one or more of resin porous carbon, bioporous carbon, petroleum-based porous carbon and coal-based porous carbon; the silane gas is monosilane or disilane; and the inert gas is nitrogen or argon.

3. The silicon-based negative electrode composite material according to claim 1, characterized in that: In step S2, chemical vapor deposition is performed on the surface of the porous silicon-carbon material to obtain the porous silicon-carbon coated with a carbon layer, comprising: placing the porous silicon-carbon material in a chemical vapor deposition furnace, introducing an inert gas at a rate of 1 to 20 L / min, heating to 500 to 800° C., and then introducing acetylene gas at a rate of 1 to 10 L / min for a ventilation time of 50 to 500 min to obtain the porous silicon-carbon coated with the carbon layer; Wherein, the inert gas is nitrogen or argon.

4. The silicon-based negative electrode composite material according to claim 1, characterized in that: In step S3, the heating method is water bath heating, and the heating temperature is 60-80°C.

5. The silicon-based negative electrode composite material according to claim 1, characterized in that: In step S3, the calcination temperature is 300-600° C., and the calcination time is 2-4 hours.

6. Use of the silicon-based negative electrode composite material according to any one of claims 1 to 5 in a lithium-ion battery.

Citation Information

Patent Citations

  • Preparation method of aluminum oxide coated silicon cathode material

    CN105958023A

  • Nano silicon-carbon composite anode material for lithium ion batteries, and preparation method of nano silicon-carbon composite anode material

    CN107845797A

  • Silicon negative electrode material with porous coating layer and preparation method thereof

    CN114695847A

  • Double-shell silicon-carbon composite negative electrode material and preparation method and application thereof

    CN117712359A

  • Surface-coated silicon-carbon composite material, method for manufacturing a surface-coated silicon-carbon composite material, anode electrode and electrochemical storage device

    EP4261931A1